APLIKASI LIMBAH KAYU SEBAGAI MATRIK/ ACUAN PADA PENCIPTAAN KARYA SENI GRAFIS TEKNIK CETAK TINGGI BERBASIS FALSAFAH JAWA - adi, sigit purnomo; Sukerta, Pande Made; Marianto, Martinus Dwi; Hadi, Sri (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2022)
Relief print is a printmaking technique that is quite well known among the public. Relief print is considered static. This creation research aims to produce novelty by combining wood waste, references/matrixes in woodcut and Aja Dumeh's Javanese philosophy with artistic creation process methods: experimentation, reflection and creation of works. The creation of this matrix or reference is expected to be able to combine wood waste, reference/matrix in Relief print with Aja Dumeh's Javanese philosophy so that the resulting work is able to campaign about the importance of protecting the environment and also preserving culture, especially Javanese culture, so that it is expected to be able to compete in the international world. The results of this creation research have creations and innovations in the form of references/matrixes used in woodcut which come from Javanese philosophy conceptually and wood waste materially